Barriers in Infection Control Practice against COVID-19: A Survey of Healthcare Workers in Benghazi Medical Centre - Naeima Houssein; Kamla Othman; Fatma Mohammed; Aeiad Saleh; Hanan Sunaallah (AlQalam Journal of Medical and Applied Sciences, 2020)
Background and objective. COVID-19 pandemic represents a public health emergency over the world. The only way to fight this novel virus is by following the standard prevention precautions. Healthcare workers in Libya face considerable challenges during the ongoing COVID-19. Barriers in infection control practice of infectious diseases are determined by many factors. This study aimed to explore attitudes of health care workers in Benghazi Medical Centre regarding barriers in infection control practice against COVID-19 outbreak. Methods. A cross-sectional survey was conducted from July 1st to July 25th 2020, involving a total of 400 HCWs across medical and allied medical professions in Benghazi medical centre. Results. Of those surveyed, 40.6% were in frontline, only half of them (51.3%) attended hand hygiene formal training in the last 3 years. The presence of all the mentioned barriers in work environment were perceived by 37.20% of participants. Limitation of personal protective equipments as a barrier was perceived by16.30% of participants. Conclusion: Attendance of formal hand hygiene training was limited in many medical and allied medical professions. For effective implementation of infection prevention practice in health care settings, barriers should be considered from the ministry of health and health care workers.